Ichimoku Cloud and Japanese Candlestick Prediction Combination Pattern Approached: The Case Study of Malaysia Stock Market - maarof, zulariffin; Lee Yee, Lynn; Liau Mei, Hui; Isharuddin, Lydia (Multidisciplinary Applied Research and Innovation, 2021)
This study presents a research on development of combination analysis of technical forecasting chart pattern based on price movement to determine buy and sell signal for trading or investment. Stock market prediction is important and of great interest because successful prediction of stock prices may promise attractive benefits. It is crucial for the traders and investors to decide an entry point and exit point to buy and sell stock in a short time period. However, relying on a single chart pattern can be tough when deciding for entry and exit point. In this research, we opt to study the effectiveness of combination chart pattern of Ichimoku Cloud and Japanese Candlestick indicators to provide strong bullish and bearish signals. This chart pattern using actual data selected from Bursa Malaysia, and three counters which are NOTION, ADVENTA and RANHILL were selected based on high volatility which is suitable for the case study evaluating the effectiveness of combination chart pattern. Therefore, a comparative study which mainly focused on technical analysis was conducted on the performance of this combination analysis for 8 months daily data market price movement. It is found that the experimental results reveal the combination algorithm successfully forecast for short term period. Thus, this study provides a promising alternative for traders and investors dealing with the forecasting of the stock price to generate profit.